A Novel Strategy for Selective O-Methylation of Glycerol in Subcritical Methanol - Bruniaux, Sophie; Varma, Rajender S.; Len, Christophe (Frontiers in Chemistry, 2019)
A new regioselective approach has been elaborated for the selective conversion of bio-based glycerol into the monomethyl derivative using sub/supercritical methanol. The reaction was realized in batch process using three reactive components namely glycerol, methanol and potassium carbonate to produce selectively the 1-O-methylglycerol in mild yields; mechanism of the O-methylation has been delineated using labeled methanol and GC-MS experiments.